Exosomes: the future of acellular nanotherapeutics in regenerative vascularization - Dawes, Jazzmyn S.; Abdelaal, Maryam; Landmesser, Mary E.; Asgardoon, Mohammad Hossein; Waldron, Olivia P.; Park, Ji Ho; Jikaria, Neekita; Ravnic, Dino J. (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundIschemic disorders represent the world’s leading cause of morbidity and mortality and can emanate from pathology in both the macrovasculature and microvasculature. Current treatment options for macrovascular disease include surgical bypass, endovascular intervention, thrombolytic drugs, and pharmacologics (vasodilators). However, when ischemia occurs at the microvascular level, conventional vascular surgical approaches are typically not feasible. In this setting, complex reconstructive surgery may be warranted, especially if concurrent open wounds are present. Thus, new pro-angiogenic treatment strategies that facilitate microvascular regenerative vascularization and wound repair are welcome.MethodsWe present a comprehensive overview of both stem cell-derived and mature–cell-derived exosomes in the context of regenerative vascularization and wound repair, focusing on cargo mechanisms and biomaterial delivery strategies. We also highlight how materials science will be instrumental to both therapeutic delivery and development of fully acellular pro-angiogenic bioengineered exosomes. All cited studies involving exosomes complied with the International Society of Extracellular Vesicles guidelines. To assess the clinical relevance and gaps, we visited clinicaltrials.gov, where keywords “exosome” and “vascular” were searched. Other parameters such as completion status, country, and exosome type further refined our search.ResultsExosomes were found to promote angiogenesis and improved wound healing outcomes primarily via Vascular Endothelial Growth Factor, FGF2, miR-126, Wnt/β-catenin, Notch and PI3K/Akt pathways. Clinicaltrials.gov revealed only 3 out of 15 completed human exosome studies worldwide related to regenerative vascularization.ConclusionTherapies utilizing exosomes as an acellular approach to regenerative vascularization are promising, though challenges with scalability remain. Further mechanistic understanding, standardization, and controlled trials are compulsory prior to widespread human application.